Delivering on CSUCI's Promise to Transfer Students (2020)
This Impact Report is a summary and celebration of the strides California State University Channel Islands (CSUCI) has successfully made implementing a Regional Transfer Success (RTS) initiative in partnership with Ventura County Community College District (VCCCD) and Santa Barbara City College (SBCC). The collective efforts of the partners identified within this report represent a number of Title V funded programs including Project ALAS (Aligning Learning and Academic Success), Project Adelante, and Project iPATH, in addition to a number of predecessor grants that set an early foundation for transfer student success in the Ventura County and Santa Barbara regions. This report provides a culminating summary of these efforts and includes:•Background on the participating institutions;•An overview of the crisis transfer students are facing;•Snapshots of the innovative programs, strategies, and policies CSUCI has put into practice along the transfer pathway;•Profiles of the faculty, administrators, and, most importantly, students who continue to make this initiative a success; and•Recommended resources and suggested next steps. We hope this report will provide faculty, administrators, and staff at other California post-secondary education institutions with insight, inspiration, and proven tactical practices to generate authentic equitable transfer pathways.